Lou Sullivan Diaries (1970-1980) and Theories of Sexual Embodiment Making Sense of Sensing - Rodemeyer, Lanei M. (Crossroads of Knowledge,, 2018)
This book highlights the intersection between theory and lived experience, academic description and the personal narrative of Lou Sullivan. Sullivan puzzled in his diaries over the conundrum of his desire to transition from female to male in order to be a gay man. The reader will follow Sullivan as he struggles with his feelings of maleness, in his troubled relationship with his lover, Tom, through his many sexual escapades, and finally, as he begins taking hormones. Alongside the diaries is an engagement with body and gender theories, accessible to the introductory reader, yet also taking up current debates especially in transgender studies. .